TRANSFORMATIONAL LEADERSHIP OF PRIVATE SCHOOL ADMINISTRATORS IN PATHUMTHANI - Usub, Thitiporn; Phetsombat, Pimolpun (Journal of MCU Nakhondhat, 2021)
The objectives of this research article were 1) to examine current and desirable conditions of transformational leadership of private school administrators in Pathum Thani, and 2) to investigate guidelines for the development of transformational leadership of school private school administrators in Pathumthani. The sample of this research consisted of 335 private school teachers in Pathum Thani selected using simple random sampling method. The informants from the interviews were seven school administrators in Pathum Thani who had a Master’s Degree in Educational Administration and held in administrative positions of educational institutions for 7 years or more. The research instruments were questionnaires and interview forms. The research was analyzed through frequency, percentage, mean, standard deviation, PNImodified and content analysis. The research findings were as follows. 1) The current and desirable conditions of transformational leadership of private school administrators in Pathum Thani were at a high level. 2) The guidelines for the development of transformational leadership of private school administrators in Pathumthani included the following: 1) intellectual stimulation. Stimulate creativity Exchange methods for solving 2) To take into account individuals, individuals should interact with staff within the school, provide advice, consult with help. Promoting people 3) in the field of inspiration Study the needs of individual personnel 4) in the field of ideological influence. Exchange of work needs or problems 5) In the field of characteristics, analyze and evaluate the ability of personnel. Find information to learn more or how to improve yourself 6) The creation of barbarians should be a good, fair, fair example. 7) In the field of vision, there should be communication to know which direction the school future must go and share the main goals, as well as understand the guidelines.